Microencapsulação de Lactobacillus acidophilus e Lactiplantibacillus plantarum em alginato e gelatina: estudo da produção, caracterização e estabilidade visando aplicação em alimentos - Silva, Sebastião Ânderson Dantas da (2021)
Probiotics are defined as viable microorganisms when ingested regularly, provide numerous health benefits. However, cell viability can be compromised by exposure to storage and the digestive process. Thus, encapsulation appears as a technological solution capable of promoting protection, controlled release, and preservation of bioactive effects. In this context, the present study aimed to produce, characterize and evaluate the stability of microparticles based on sodium alginate and/or porcine gelatin containing Lactobacillus acidophilus NRRL B-4495 and Lactiplantibacillus plantarum NRRL B-4496. Encapsulation was performed using the oil-in-water (O/W) emulsification technique, using Tween 20 as a surfactant. The encapsulates obtained were characterized by Scanning Electron Microscopy (SEM), Laser Diffraction, Fourier Transform Infrared Spectroscopy (FTIR), and X-ray Diffraction (XRD). Furthermore, they were evaluated for cell viability, incorporation efficiency, water dispersibility, thermal stability, and stability during storage for 120 days under different temperature conditions (5 °C and 25 °C). For those encapsulated in gelatin, the micrographs showed irregular particles with a smooth surface containing microorganisms in their structures, unlike the sodium alginate-based particles, which showed shrinkage and an apparent absence of microorganisms. Gelatin-based formulations containing L. acidophilus and L. plantarum had mean diameters of 26.08 (1.74) μm and 21.56 (4.17) μm, while alginate particles exhibited diameters of 5.24 (1.32) μm and 5.52 (4.55) µm. The FTIR indicated chemical interactions between the constituents of gelatin-based formulations, with new vibrational bands and visualization of characteristic bands of probiotics, this being not observed in alginate encapsulates. The XRD results showed that L. acidophilus and L. plantarum encapsulated in gelatin presented a semi-crystalline structure. In addition, encapsulated in gelatin showed viability of 10.9 (0.9) Log CFU/g and 9.9 (0.8) Log CFU/g and encapsulation efficiencies of 89.6% (4.2) and 81.1% (9.7) (p > 0.05). However, the cell viability and efficiency of incorporation of the alginate-based probiotic microparticles were null. Water dispersibility of 69.9% (9.7) and 69.0% (8.4) were found for L. acidophilus and L. plantarum encapsulated in gelatin was found for gelatin encapsulates. Thermal analysis indicated stability at a temperature below 54 ºC, suggesting preservation of the microparticles at room temperature. Finally, the L. acidophilus microparticles in gelatin were stable for 120 days of storage at 5 ºC [12.2 (0.1) Log CFU/g] and 25 ºC [10.7 (0.6) Log CFU/g] (p > 0.05). Thus, it was found that microencapsulation in gelatin by O/W emulsification is an adequate and favorable strategy for the protection and stability of probiotic bacteria, enabling future applications in the food area.